Fictional storytelling in the medieval eastern Mediterranean and beyond - Cupane, Carolina; Krönung, Bettina (Brill's companions to the Byzantine world, 2016)
This volume offers an overview of the rich narrative material circulating in the medieval Mediterranean. As a multilingual and multicultural zone, the Eastern Mediterranean offered a broad market for tales in both oral and written form and longer works of fiction, which were translated and reworked in order to meet the tastes and cultural expectations of new audiences, thus becoming common intellectual property of all the peoples around the Mediterranean shores. Among others, the volume examines for the first time popular eastern tales, such as Kalila and Dimna, Sindbad, Barlaam and Joasaph, and Arabic epics together with their Byzantine adaptations. Original Byzantine love romances, both learned and vernacular, are discussed together with their Persian counterparts and with later adaptations of western stories. This combination of such disparate narrative material aims to highlight both the wealth of medieval storytelling and the fundamental unity of the medieval Mediterranean world. Contributors are Carolina Cupane, Faustina Doufikar-Aerts, Massimo Fusillo, Corinne Jouanno, Grammatiki A. Karla, Bettina Krönung, Renata Lavagnini, Ulrich Moennig, Ingela Nilsson, Claudia Ott, Oliver Overwien, Panagiotis Roilos, Julia Rubanovich, Ida Toth, Robert Volk and Kostas Yiavis.